Working poverty, nonstandard employment and political inclusion. Issue 2 (23rd February 2022) - Marinova, Dani M.
Abstract: Are labour market outsiders also political outsiders? The labour market dualization literature offers inconsistent evidence as to the effects of nonstandard employment on political demobilization. This article shows that thus far unaccounted for exposure to poverty among workers in nonstandard employment varies considerably across labour markets, and that this variation carries implications for political inclusion. Analyses of five waves of the European Social Survey indicate that exposure to working poverty absorbs much of the predictive power of nonstandard employment, suggesting that working poverty, rather than labour market per se, leads to political demobilization. The findings help explain the hitherto inconsistent results in studies of labour market dualization and lend support to the argument that future research should account for cross-national variation in working poverty.